The Influence of Digital Marketing and Consumer Trust on Interest in Buying Local Products Through Social Media on the People of Ambon City - Saptenno, Sammy; Ferdinandus, Leonora (Digital Innovation : International Journal of Management, 2026)
The development of digital marketing through social media has changed people's consumption patterns, including in the marketing of local products, but empirical studies in Eastern Indonesia such as Ambon City are still very limited. This study aims to analyze the influence of digital marketing and consumer trust on the interest in buying local products through social media in the people of Ambon City, both partially and simultaneously. The approach used was quantitative with a causal associative design, involving 120 respondents selected through purposive sampling techniques, with data collected through a Likert scale questionnaire  and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS). The test results showed that digital marketing had a positive and significant effect on buying interest (β=0.46; t=7.62; p=0.000), as well as consumer confidence (β=0.41; t=6.83; p=0.000). Together, the two variables were able to explain 71% of the variation in buying interest (R²=0.71), so that all research hypotheses were accepted. These findings confirm that the effectiveness of promotional content and brand interaction on social media needs to be accompanied by strengthening consumer trust in order to be able to encourage interest in purchasing local products optimally. This research makes a theoretical and practical contribution to the development of trust-based digital marketing strategies in regional contexts with distinctive socio-cultural characteristics such as Ambon City.